2023
DOI: 10.1021/acs.cgd.2c01374
|View full text |Cite
|
Sign up to set email alerts
|

Four Novel Cobalt(II) Coordination Polymers Based on Anthracene-Derived Dicarboxylic Acid as Multi-functional Fluorescent Sensors toward Different Inorganic Ions

Abstract: A series of Co(II)−H 2 L coordination polymers were prepared with different auxiliary ligands, namely {5-{(anthracene-9-ylmethyl)-amino}isophthalic acid, bibp = 4,4′-bis(imidazolyl)biphenyl, bpy = 2,2′-bipyridine, bipd = 3,5-bis(1-imidazoly)pyridine, and bbibp = 4,4′-bis(benzoimidazo-1-yl)biphenyl), by a similar solvothermal method. X-ray diffraction analyses revealed that 1, 3, and 4 exhibit a two-dimensional (2D) structure, which further builds the threedimensional (3D) supramolecular architecture via the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Single-crystal X-ray crystallography analysis revealed that 1 was crystallized in the trigonal space group R 3̄ (Table 1). The crystal structure of 1 shows a six-coordinate geometry around the indium centre, coordinated with three oxime oxygen atoms (O1) and three carbonyl oxygen atoms (O2) from three partially deprotonated ligands, which adopts a distorted trigonal prism coordination geometry and was confirmed by the continued shape measurement (CShM) 30,32,33 analysis (Fig. 1b); the results are listed in Table S1 †.…”
Section: Resultsmentioning
confidence: 77%
“…Single-crystal X-ray crystallography analysis revealed that 1 was crystallized in the trigonal space group R 3̄ (Table 1). The crystal structure of 1 shows a six-coordinate geometry around the indium centre, coordinated with three oxime oxygen atoms (O1) and three carbonyl oxygen atoms (O2) from three partially deprotonated ligands, which adopts a distorted trigonal prism coordination geometry and was confirmed by the continued shape measurement (CShM) 30,32,33 analysis (Fig. 1b); the results are listed in Table S1 †.…”
Section: Resultsmentioning
confidence: 77%
“…A summary of the sensing of Fe 3+ , Cr 3+ and Al 3+ ions using MOF materials is shown in Tables S6–S8 (ESI†), respectively. 52,59,89–120…”
Section: Resultsmentioning
confidence: 99%
“…Single-crystal X-ray analysis indicated that 1 crystallized in the triclinic system P1̅ space group and featured a 3D supermolecular structure with two S2), which are comparable to those reported for other Co-based MOFs. 11,30,31 Interestingly, the interconnection of adjacent {Co3O S3). In 2, Co(II) ions are bridged by H 2 TTHA 4− and bidpe to form a tangled one-dimensional (1D) structure consisting of one infinite zigzag [Co− H 2 TTHA] n chain and two wavy [Co-bidpe] n chains, as shown in Figure 2b.…”
Section: Synthesis Of {[Comentioning
confidence: 99%